1997
DOI: 10.1097/00000372-199708000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Metaplastic Synovial Cyst in an Ehlers-Danlos Patient

Abstract: Metaplastic synovial cyst is a recently reorganized entity characterized by a cystic space lined by polygonal cells and villous structures resembling synovium pointing toward the lumen. It usually develops following trauma. We report a 15-year-old girl with Ehlers-Danlos syndrome who developed a nodular lesion of her elbow without previous trauma. Histopathological and immunohistochemical studies yielded results similar to those reported in cases of cutaneous metaplastic synovial cyst. This case appears to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 7 publications
2
21
0
Order By: Relevance
“…They usually appear in areas of previous trauma or scars. A similar lesion has been reported only once in an EDS patient 5 and was interpreted as a consequence of the genetically determined fragility of the skin in these patients. The same authors provided a detailed discussion of the pathogenesis and mechanism of cyst formation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…They usually appear in areas of previous trauma or scars. A similar lesion has been reported only once in an EDS patient 5 and was interpreted as a consequence of the genetically determined fragility of the skin in these patients. The same authors provided a detailed discussion of the pathogenesis and mechanism of cyst formation.…”
Section: Discussionsupporting
confidence: 76%
“…Few more cases have been published; the more recent reports are those by Goiriz et al, 2 Ramdial et al, 3 and Chakravarthy et al 4 In one patient affected with a cutaneous metaplastic synovial cyst, a diagnosis of EDS was also established. 5 We report a second case of a cutaneous metaplastic synovial cyst in a patient affected with EDS.…”
Section: Introductionmentioning
confidence: 89%
“…Although the exact cause of CMSC has remained unclear, 13 of 23 reported cases have had histories of local trauma. Further, three of ten cases that have occurred spontaneously without local trauma were accompanied by Ehlers-Danlos syndrome3,10,12, which led us to believe that abnormal healing after microtrauma was a pathogenic mechanism of CMSC. Additionally, the fact that four cases of CMSC have accompanied rheumatoid arthritis6,9 and arthrosis10 suggested that chronic inflammation, constant pressure, and repeated manipulation have played critical roles in the pathogenesis of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology is not proven, a history of preceding surgery or trauma was present in most cases1-7, and some cases occurred in patients with basal cell carcinoma12, Ehler-Danlos syndrome13 and rheumatoid arthritis14. The duration between the time of trauma and the onset time of CMSC ranges from a few weeks to a few years.…”
Section: Discussionmentioning
confidence: 99%